International and Domestic Commodities and the Theory of Prices - Zapoleon, L. B. (Quarterly Journal of Economics, 1931)
The assumption of independent national price systems, in theory and in treatment of current problems, 409. — I. No domestic and no international prices; only local prices, more or less sensitive to external conditions, 410; merchandise and services, wholesale and retail prices, not differentiated in the terms "international" and "domestic" commodities, 413. — II. Parallelism in movement of wholesale price indices, 413; Internationalization of the commodity price structure, 414. — III. Illusion of domestic price structure for wholesale merchandise: large or sustained movement not essential to price interdependence, 422; defective market data and apparent price deviations, 432; limitations upon actual deviation; a priori indications of high correlation, 433. — IV. Reformulation: the local category consists mainly of services and retail prices, 436; merchandise at wholesale is international, 437; regional prices structurally related, 442. — V. Practical applications: farm relief, 452; export combinations, 453; tariff and monetary problems, 455. — VI. Regional prices of international goods: as affected by foreign exchange, 456; by movement of specie or changes in purchasing power, 457; a possible reconciliation with orthodox theory, 458; price stabilization through credit policies of central banks, 459.